2018
DOI: 10.1590/1413-785220182605199995
|View full text |Cite
|
Sign up to set email alerts
|

Bone Tunnel Enlargement With Non-Metallic Interference Screws in Acl Reconstruction

Abstract: ObjectiveTo compare the widening of bone tunnels between poly-etheretherketone (PEEK), absorbable polylactic acid DL (PLDL) and tricalcium phosphate (TCP) interference screws in anterior cruciate ligament (ACL) reconstruction.MethodsThree groups of patients undergoing ACL reconstruction with at least 1 year of follow-up using the out-in drilling technique and hamstring as a graft were assessed. The patients were divided according to the type of interference screw used (PEEK, PLDL and TCP). Computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…De Padua uses arthroscopic technology to clean the radial wrist short extensor joint and at the same time decorticalizes the external epicondyle. The results show that the same treatment effect as open surgery can be achieved, but arthroscopic surgery has fewer complications and the movement can be earlier to restore life [ 9 ]. Niki reported that the arthroscopic radiofrequency cleaning of the joint capsule and the radial wrist short extensor joint can resume work in an average of 2.2 weeks after the operation, and the grip strength can reach 96% of the contralateral side [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…De Padua uses arthroscopic technology to clean the radial wrist short extensor joint and at the same time decorticalizes the external epicondyle. The results show that the same treatment effect as open surgery can be achieved, but arthroscopic surgery has fewer complications and the movement can be earlier to restore life [ 9 ]. Niki reported that the arthroscopic radiofrequency cleaning of the joint capsule and the radial wrist short extensor joint can resume work in an average of 2.2 weeks after the operation, and the grip strength can reach 96% of the contralateral side [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, FTE occurred regardless of whether bioabsorbable or metal screws were used [ 10 , 17 19 ]. This has also been observed in relation to anterior cruciate ligament reconstruction (ACLR) [ 23 ]. However, a titanium screw was used in one study only [ 19 ].…”
Section: Discussionmentioning
confidence: 77%
“…Combining this with our results we've serious concerns about the bony ingrowth and ossification capacity of bioabsorbable screws. Besides all these bioabsorbable screws there are also novel studies with polyether-ethyl ketone (PEEK) screws, but these are showing the same amount of tunnelwidening (17) as the PLLA-BCP screws.…”
Section: Discussionmentioning
confidence: 99%